2015
DOI: 10.5811/westjem.2015.1.23272
|View full text |Cite
|
Sign up to set email alerts
|

Young Patients with Suspected Uncomplicated Renal Colic are Unlikely to Have Dangerous Alternative Diagnoses or Need Emergent Intervention

Abstract: IntroductionIn the United States there is debate regarding the appropriate first test for new-onset renal colic, with non-contrast helical computed tomography (CT) receiving the highest ratings from both Agency for Healthcare Research and Quality and the American Urological Association. This is based not only on its accuracy for the diagnosis of renal colic, but also its ability to diagnose other surgical emergencies, which have been thought to occur in 10–15% of patients with suspected renal colic, based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Many reports point out that cumulative radiation exposure increases cancer risk, and young patients are at a higher risk from diagnostic X-rays than adults [5,21]. Schoenfeld et al indicated that in younger patients with uncomplicated renal colic, the benefit of immediate CT for suspected renal colic is questionable [22]. Nevertheless, nearly six out of seven patients with a diagnosis of renal colic in the emergency department still underwent a CT scan, and in patients with previous ED visits for renal colic, the CT rate was still 59% [20].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports point out that cumulative radiation exposure increases cancer risk, and young patients are at a higher risk from diagnostic X-rays than adults [5,21]. Schoenfeld et al indicated that in younger patients with uncomplicated renal colic, the benefit of immediate CT for suspected renal colic is questionable [22]. Nevertheless, nearly six out of seven patients with a diagnosis of renal colic in the emergency department still underwent a CT scan, and in patients with previous ED visits for renal colic, the CT rate was still 59% [20].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of renal point-of-care limited ultrasonography modestly improved risk stratification of the STONE score [31]. Age and elevated white blood cell count are known predictors of ureteral stone requiring urologic intervention [17,32]. A prior history of kidney stone is known to increase the risk of ureteral stone in patients with suspected kidney stone [33].…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed prior studies of clinical decision rules and studies identifying predictors of ureteral stones requiring intervention or serious alternative diagnoses [7,1619]. Important predictors of stone requiring urologic intervention from the literature review included stone size, stone location, pain level, signs of urinary tract infection (elevated white blood cell count, leukocyte esterase and nitrites on urinalysis), and age.…”
Section: Methodsmentioning
confidence: 99%
“…Such differences may have marked implications for the applicability of available evidence. As shown in meta-analyses and systematic reviews, renal colic due to stone size 5–10 mm in the lower ureter may benefit more from tamsulosin use by facilitating stone passage than the stones located higher in the urinary tract or with size out of this range [ 15 , 16 ]. Therefore, we recommend increased use of tamsulosin for patients in Qatar who have larger stone size 5–10 mm in the lower ureter to get maximum benefits of MET [ 7 , 8 , 17 ].…”
Section: Discussionmentioning
confidence: 99%